ETHNOBOTANICAL SURVEY OF PHOENIX DACTYLIFERA L. POLLEN USED FOR THE TREATMENT OF INFERTILITY PROBLEMS IN ALGERIAN OASES - Selmani, Cherifa; Chabane, Djamila; Bouguedoura, Nadia (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The Phoenix dactylifera L. (date palm) is known for its traditional medicinal properties across the history of native population in Algerian Sahara. There is a large trend of consumption of date palm pollen preparations in many human infertility cases in our country. However, the validity has not been scientifically tested. There has been no direct scientific research on this application. This study was undertaken to identify cultivars with greater potential in the traditional medicine uses. To evaluate the effects of da palm pollen on some sexual behavioural parameters of male adult rats, we tested the role of pollen powder from Deglet Nour cultivar on some male reproductive parameters. Materials and Methods: An Ethnobotanical survey was conducted in 17 oases in southern Algeria to identify all cultivars with medicinal interest. Local people were interviewed with open questions. A questionnaire and personal interviews for data collection were designed to record important cultivars, parts used and preparations. To determine the active constituents of date palm pollen used in traditional medicine, a phytochemical screening was performed. The effects of oral administration of date palm pollen suspension on male adult rats were investigated on body and testicle weights, serum testosterone level. Results: 131 prominent cultivars were found within 12 cultivars containing various parts with medicinal effects. Some primary and secondary metabolites were detected by phytochemical screening. The pollen increased the weight of the body, testicles and enhanced the serum testosterone level of male rats treated. Conclusion: The present survey has provided the identification and recognition of date palm cultivars used in traditional Saharan medicine. Date palm pollen could improve sexual activities in male infertility cases and may be attempted to derive drugs.